Effect of Triptolide on Dextran Sodium Sulfate-Induced Ulcerative Colitis and Gut Microbiota in Mice - Wu, Hao; Rao, Quan; Ma, Guang-Chao; Yu, Xiao-Hong; Zhang, Cong-En; Ma, Zhi-Jie (Frontiers in Pharmacology, 2020)
Triptolide is beneficial for the treatment of ulcerative colitis (UC), which is closely related to the gut microbiota. However, whether the therapeutic effects of triptolide involve the regulation of the gut microbiota is still unclear. In the present study, animal models of UC mice induced by dextran sodium sulfate (DSS) were established, the changes of gut microbiota in mice were detected by high-throughput sequencing. The effects of triptolide on DSS-induced UC mouse and its gut microbiota were studied. As a result, we found that triptolide exerted anti-inflammatory and therapeutic effects on UC mice. Sequencing results for the gut microbiota showed that the composition of the gut microbiota from DSS group was disordered as compared with that from the control group, consistent with a decrease in the abundance of flora. Triptolide treatment accelerated the recovery of the population of the gut microbiota and significantly improved the microbial diversity. At the phylum level, the population of Bacteroidetes decreased and that of Firmicutes increased. At the genus level, Bacteroides and Lachnospiraceae counts decreased. Thus, triptolide could regulate the composition of the gut microbiota, accelerate the recovery of microbiota, and exert good therapeutic effects in UC mice. Our results also revealed that fecal transplantation from triptolide-treated mice could relieve UC. This study provides a reference for the rational use of triptolide for the treatment of UC.